Electrical, photoelectrical and morphological properties of ZnO nanofiber networks grown on SiO2 and on Si nanowires - Nadia Celeste Vega; Monica Tirado; David Comedi; Andres Rodriguez; Tomas Rodriguez; Gareth M. Hughes; Chris R. M. Grovenor; Fernando Audebert (Materials Research, 2013)
ZnO nanofibre networks (NFNs) were grown by vapour transport method on Si-based substrates. One type of substrate was SiO2 thermally grown on Si and another consisted of a Si wafer onto which Si nanowires (NWs) had been grown having Au nanoparticles catalysts. The ZnO-NFN morphology was observed by scanning electron microscopy on samples grown at 600 °C and 720 °C substrate temperature, while an focused ion beam was used to study the ZnO NFN/Si NWs/Si and ZnO NFN/SiO2 interfaces. Photoluminescence, electrical conductance and photoconductance of ZnO-NFN was studied for the sample grown on SiO2. The photoluminescence spectra show strong peaks due to exciton recombination and lattice defects. The ZnO-NFN presents quasi-persistent photoconductivity effects and ohmic I-V characteristics which become nonlinear and hysteretic as the applied voltage is increased. The electrical conductance as a function of temperature can be described by a modified three dimensional variable hopping model with nanometer-ranged typical hopping distances.